Engineered microneedle systems for topical cancer therapy. (April 2023) - Jiang, Xingyu; Xia, Wenzheng; Pan, Jiaxing; Yang, Wenfang; Zhang, Shunan; Li, Chunming; Zan, Tao; Lai, Yi; Xu, Zhiai; Yu, Haijun
Highlight: The types and raw preparation materials of microneedles are introduced. The definition of engineered microneedle and engineering approach (including endogenous and exogenous stimulation, structure and preparation materials) are discussed. The state-of-the-art utilization of microneedle-based technology in cancer phototherapy, immunotherapy, gene therapy, chemotherapy, and starvation therapy are highlighted. The perspectives and clinical translation challenge of engineered microneedles are addressed. Abstract: In past years, microneedle (MN)-mediated transdermal drug delivery has paved a new way for cancer therapy. MN is a local drug delivery method that can reduce systemic drug exposure and enrich drug concentration at the lesion site, resulting in the decrease of therapeutic agent-associated side effects with attendant improvement in therapeutic efficacy. On the basis of these characteristics, MNs can be further endowed with a variety of functions to achieve smart drug release such as light response-controlled release. In this review, we provided an overview of the cutting-edge progress about engineered MN-based transdermal drug delivery. Starting from a brief introduction of types of MNs and methods for the fabrication, we then detailed the recent advances of the engineered MNs for tumor therapy, covering a brief overview of the biomedical application of engineered MNs in other diseases. Discussions on the current limitations and future perspectives with respect to clinical translation of engineered MNs for cancer therapy were finally put forward. It is expected that this review will promote and strengthen the engineering and deployment of MNs for cancer therapy. Graphical abstract: In this review, we summarized the cutting-edge advances of engineered MNs for cancer therapy encompassing raw materials for MNs preparation and structural design. The state-of-the-art utilization of MN-based technology in cancer phototherapy, immunotherapy, gene therapy, chemotherapy, and starvation therapy were described in concrete detail. Image, graphical abstract